(untitled) (Journal of International Studies, 2014)
Энэхүү өгүүлэлд Зүүн хойд Азид Орос, Хятадын явуулж буй бодлого үйл ажиллагааны үндсэн чиглэл, ялангуяа худалдаа, эдийн засаг, хөрөнгө оруултын салбарын хамтын ажиллагаа, түүний өнөөгийн болон цаашдын төлөв байдлыг хураангуйлан авч үзсэн. Хоёр хөрш маань энэ бүс нутагт дангаараа эдийн засгийн өрсөлдөөнд орохоосоо илүүтэй зах зээлийн бүсчилсэн хөгжилд тулгуурлаж, бодлого үйл ажиллагаагаа аль болох уялдуулан зохицуулах болсныг тал бүрээс нь харуулж, дүн шинжилгээ хийхийг оролдсон. Role of Russia-China strategical partnership in Northeast Asia integration The Peace and stability in the Northeast Asia region depends in many ways on the state of relations between the Russian Federation and the People’s Republic of China. Then, we must be happy in this region because Russia and China, in pursuing their own interests, sometimes compatibles and sometimes incompatibles, are trying to live peacefully at least now. The foreign policy of Russia is directed to regain its influence in the Far East, once dominated for the USSR. In doing this, Russia is relying in its huge mining, especially in oil resources. Precisely, Russia is trying to do the same concerning the Northeast Asia. China, on the other side, is making efforts directed to gain influence in the Far East. Russia and China are cooperating side by side in this region. They are discussing and putting in place mega projects of cooperation. The bilateral investments increased constantly. During the visit of Chairman Xi to Moscow important agreements were signed of an amount of 650 billion us dollars. The two sides say that the two countries are “eternal friends and not eternal enemies”.